Bulk-driven fully balanced second-generation current conveyor in 0.18 µm CMOS - Kumngern, Montree; Khateb, Fabian; Kulej, Tomasz (My University, 2019)
This paper presents an ultra-low-voltage and low-power fully balanced second-generation current conveyor (FBCCII) which is suitable for applications in ultra-low-voltage and low-power analog circuits. To confirm the attractive features of proposed FBCCII, the analog circuits such as fully digital programmable voltage gain amplifier, fully all-pass sections, fully band-pass filter and fully universal filter using the proposed FBCCII as active element have been proposed. The performances of the proposed FBCCII and its applications can be depicted through simulation results using SPICE simulations and 0.18 µm n-well CMOS process from TSMC with a 0.5 V supply.
Keywords: Analog circuit; Bulk-driven transistor; Fully balanced second-generation current conveyor (FBCCII); Low-voltage low-power circuit